Pengaruh status penguasaan lahan dan adopsi teknologi terhadap produksi padi sawah di provinsi sentra padi di Indonesia: The influence of land tenure and technology adoption on lowland rice production in central rice-producing provinces in Indonesia - Ariani, Mewa; Tarigan, Herlina; Suhartini, Sri Hastuti; Ariningsih, Ening; Sumedi,; Savitri, Sheila; Suryani, Erma; Mardianto, Sudi; Sunarsih, (Analisis Kebijakan Pertanian, 2025)
The 2023 Agricultural Census reveals a rising number of smallholder farmers, leading to the adoption of adaptive land management strategies through non-ownership-based land tenure. These land tenure arrangements influence input and technology use decisions, which potentially reduce rice production. This study aims to analyze the effects of land tenure status and technology adoption on lowland rice production. A survey was conducted in 2021 across ten central rice-producing provinces in Java and off-Java, covering 20 regencies, 39 sub-districts, and 1,950 farmer respondents selected based on the proportion to land tenure status. Data were analyzed using descriptive analyses and multiple linear regression with a Cobb-Douglas production function. The findings of this study indicate that not all landowner farmers cultivate their own land due to capital and labor constraints. Instead, the land is cultivated by relatives or trusted individuals within the same village through leasing, sharecropping, or pawning arrangements. While most farmers have adopted certified improved seed, chemical fertilizers, and agricultural machinery, the tegel planting system remains dominant. Regression results show that seeds and fertilizers significantly and positively affect rice production, whereas leased and pawned land tenure exhibit inverse effects. The recommendation from this study is that to achieve rice self-sufficiency, the volume of subsidized seed and fertilizer assistance per hectare be increased and the number of farmers receiving assistance expanded, especially outside Java. In addition, extension services for non-landowner farmers are necessary to enhance their understanding of the importance of using appropriate rice farming technologies to improve productivity and income.
Keywords: land tenure systems; paddy fields; rice production; technology adoption; food security